Simulation of accelerated strip cooling on the hot rolling mill run-out roller table - U. Muhin; S. Belskij; E. Makarov; T. Koynov (Fracture and Structural Integrity)
A mathematical model of the thermal state of the metal in the run-out roller table continuous wide hot strip mill. The mathematical model takes into account heat generation due to the polymorphic ? ? ? transformation of supercooled austenite phase state and the influence of the chemical composition of the steel on the physical properties of the metal. The model allows calculation of modes of accelerated cooling strips on run-out roller table continuous wide hot strip mill. Winding temperature calculation error does not exceed 20°C for 98.5 % of strips of low-carbon and low-alloy steels